PENGETAHUAN DAN SIKAP ODHA (ORANG DENGAN HIV DAN AIDS) TENTANG HIV DAN AIDS DAN PENCEGAHANNYA - Dewi Rokhmah; Khoiron Khoiron (Jurnal Ilmu Kesehatan Masyarakat, 2013)
AIDS is spreading both in numbers and geographic area, it is revewed as a major public health threat and stategies are underway to increase AIDS awareness and knowledge among general public include from PLHA.In Indonesia, HIV/AIDS programmes still less in PLHA included, because of stigma and discrimination in society.Included PLHA in intervention planning, is the efective strategy in reducing stigma and discrimination and increasing commitment to change policy and supporting environment in HIV/AIDS programmes. The aims of this research is analizing knowledge and attitudes of PLHA about HIV/AIDS and its prevention.Thisresearch used descriptivemethod. The population is PLHA in Banyuwangi Regency, and affordable target is PLHA who visit and get service in VCT of Genteng Hospital in Juni-July 2012. Sample is collected with consecuttve sampling to all subject compleded collection criteria. Collected data was analyzed descriptively with table and naration.This research showed  that the amount of respondents was men, aged more than 30years, have married, and graduated from senior and junior high shcool, and as PLHA  since 1-5 years, with risk factors from heterosex without condom, IDU, infant from the mother and homosex (gay/lesbian).All of respondents have high knowledge about HIV/AIDS and its prevention efforts, consist of meaning, causes, transmission, prevention and terapy of HIV/AIDS. The numbers of respondents have positive attitudes towards HIV/AIDS and its prevention efforts, showed by statement supported to prevention behaviour of HIV/AIDS, specifically: faith to one partner, use condoms in sexual intercourse, check to health provider, and HIV/AIDS can spread and cause death.The increasing of knowledge and attitudes about HIV/AIDS of PLHA and society is needed as involvement at HIV/AIDS prevention programme by behaviour change from risk to healthy behaviour in order to reduce stigma and discrimination in PLHA. Keywords : Attitudes, Knowledge, PLHA, HIV & AIDS